The Urgency of Social Potential Mapping of Women in The Coastal Area to Decrease Poverty - Mansyur Radjab; Syamsuddin Simmau (Hasanuddin Journal of Sociology, 2019)
The result of this study is really meaningful to reduce the poverty of women who living in the coastal area. Poverty is the global issue that must be decreased sustainably until 2030 based on the United Nation Sustainable Development Goals (SDGs), especially for women living in the coastal area. The major objective of this study is to determine the social potential of women in the coastal area in order to reduce their poverty. The method used is mixed (quantitative and qualitative) method. There are 84 sample of this study. Data collected by using questioner and depth interview. The results of this study determined that the first important thing in reducing poverty of women in the coastal area is to map social potentials. The other urgent finding is lack of education, lack of skill, and women as un-supposed worker are the inhibiting factors of women to develop socially. On the other hand, the social potentials of women are; young worker, working time productivity, and the ownership of product. Therefore, the social potential mapping is the first important action to apply before empowering women in order to function a social function for reduction poverty